Shared decision making, really patient centered care - Barani, Mariela; Kopitowski, Karin (Revista del Hospital Italiano de Buenos Aires, 2013)
Daily in our practice we happen to make decisions that have to do with people’s health. Most of them are taken in scenarios where there is more than one possible option, having each its pros and cons and also there is usually some degree of uncertainty. The decision made will impact on people’s life to different extents. In the same way that people are able to make important decisions in other aspects of their lives, knowing pros and cons of every option and taking into account their own values and preferences, it is desirable that they can do the same when it comes to their own health care. The most efficient decisions are those which are made taking into consideration people’s values and preferences, scientific evidence and context. Our role as part of a healthcare team is to encourage an open dialogue with patients, so that, once thoroughly informed and from their own perspective they can get involved in a decision making process that pertains to their health care
Keywords: shared decision making; patient centered care